2002
DOI: 10.1143/jjap.41.1691
|View full text |Cite
|
Sign up to set email alerts
|

GeSbTe Phase Change Material for Blue-Violet Laser at High Linear Speed

Abstract: In discharge denitrification, radical production by electron collision with combustion gas is a key process which determines the denitrification process and its performance. In this study N, O, OH and H radical densities have been measured by appearance mass spectrometry in a low-pressure discharge field with parallel electrodes (2 cm gap) under simulated combustion gas flow. Also, electric field, electron number density and electron temperature at the radical sampling position have been measured by the Langmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For write-once HD-DVDs and BDs, the recording materials can be either organic dyes 1,2) or inorganic metallic alloys. 3) Phase-change-based alloys, 4) single-layer AlSi alloys, 5,6) bilayer metals such as Cu/Si 7) and Zn/Ge, 8) and metallic nitrides 9) have been reported for write-once disk applications. However, regardless of the recording material types, complicated 4 to 8 multilayer structures consisting of lower and upper dielectric layers, a recording layer, a space layer, and a reflection layer are usually required for the optical disks to ensure a reliable lifetime for data storage.…”
Section: Introductionmentioning
confidence: 99%
“…For write-once HD-DVDs and BDs, the recording materials can be either organic dyes 1,2) or inorganic metallic alloys. 3) Phase-change-based alloys, 4) single-layer AlSi alloys, 5,6) bilayer metals such as Cu/Si 7) and Zn/Ge, 8) and metallic nitrides 9) have been reported for write-once disk applications. However, regardless of the recording material types, complicated 4 to 8 multilayer structures consisting of lower and upper dielectric layers, a recording layer, a space layer, and a reflection layer are usually required for the optical disks to ensure a reliable lifetime for data storage.…”
Section: Introductionmentioning
confidence: 99%
“…At present, recording materials compatible with blue-laser recording are of particular interest. For such materials, organic ones are dyes that are sensitive to blue irradiation while inorganic ones include phase-change-based alloys, 5,6) AgInSbTe-SiO 2 nanocomposite films, 7,8) single layer metals such as AlSi alloys, 9,10) bismuth oxide (BiFeO) [11][12][13] and Bi-Fe-(N) layer, 14) and bilayer metals such as Ge/Au, [15][16][17][18] Cu/Si, 19) ZnO/Ge, 20) amorphous silicon (a-Si)/Cu, [21][22][23][24] a-Si/Al, 24,25) a-Si/Ni, [26][27][28] and Bi/Ge. 29,30) In our previous study, 14) the Bi-Fe-(N) system was demonstrated to be a promising medium for high-density write-once recording.…”
Section: Introductionmentioning
confidence: 99%
“…Both organic and inorganic materials have been proposed for write-once recording purposes. [8][9][10] The inorganic materials include phase-change-based alloys, 11) single-layer alloys such as AlSi 12,13) and Bi-Fe-(N), 14) and bi-layer metals such as Cu/Si, 15) Zn/Ge, 16) Ge/Au, 17) and Cu/amorphous silicon (a-Si). 18) Recently, nanocomposite films applied to super-resolution near-field structure (super-RENS) optical disks [19][20][21] and signal recording 22,23) have been reported.…”
Section: Introductionmentioning
confidence: 99%